Protooncogene bcl-2 in process of apoptosis. Review article - Humlová, Z (Sbornik lekarsky, 2002)
The process of apoptosis is genetically regulated form of cell death, which is tightly connected, with maintaining of tissue homeostasis in multicellular organisms. Mitochondria play a key role in this process being involved in ATP synthesis, production of oxygen free radicals, control of Ca2+ ions, extrusion of apoptogenic molecules such as cytochrome c, apoptosis inducing factor, Smac/DIABLO protein and several procaspases. Changes in the flux of ions and water across the inner mitochondrial membrane characterize the early phase of apoptosis, during which an increase in matrix volume may precede a collapse of mitochondrial membrane potential (delta psi m). These changes are suppressed by Bcl-2/Bcl-XL facilitated by Bax, and mediated at least by so-called permeability transition pore complex which is one of possible mechanisms involved in mitochondrial membrane permeabilization (MMP).
Keywords: Apoptosis; protoonkogenní proteiny c-bcl-2; apoptóza; Mitochondria; mitochondrie; Proto-Oncogene Proteins c-bcl-2